Access to Finance and Performance of Firms in the Construction Sector of Ghana - Bonful, P.E.J. (University of Ghana, 2019)
The purpose of this research study is to investigate the relationship between financial inclusion, to be specific access to finance and its impact on the performance of firms in the Construction sector of Ghana. As it is well known in the literature that financial inclusion generally has a positive influence on performance, will the results differ if the scope is narrowed down from country level to firms with similar characteristics? Firstly, the paper seeks to identify the level of financial inclusion among firms in the Construction sector of Ghana. Secondly, through the use of OLS regression methods, the relationship between financial inclusion variables and performance is analysed. Taking crosssectional data from 42 Construction firms in the Greater Accra Region registered with the Association of Builders and Contractors Ghana. The analysis showed that not all financial inclusion variables were significant to the performance of firms in the construction sector. However, agreeing with existing literature that there is a positive causality relationship between access to finance and financial performance. Heavy influences on financial performance came from long term financial services. And a discovery that regulations could greatly influence financial performance as well. These results speak loads into future policy formulation especially for a country that suffers from a great infrastructural deficit. The performance of construction firms can be greatly enhanced if these policies make firms in the sector more financially inclusive. The focus of these policies must be on long term financial service provision which will be the funds most beneficial to construction firms in Ghana.
MBA.
Keywords: Finance; Firms; Construction Sector; Ghana